Small-world networks in professional football: conceptual model and data - Gama, J.; Couceiro, M.; Dias, G.; Vaz, V. (European Journal of Human Movement, 2015)
The aim of this study was to verify whether interactions taking place between professional football players are compatible with the concept of small world networks. We observed 30 matches and analysed 7.583 collective offensive actions, since the beginning of possession of the ball to their loss, including: passes completed, passes received and crosses, involving a total of 22.518 intra-team interactions in the Portuguese Premier League, corresponding to all 2010/2011 season. The players were classified based on their tactical intervention region and movements, through four sectors: 1) goalkeepers; 2) defenders; 3) midfielders, and 4) forwards. Performance data was analysed using the Match Analysis Software Amisco® (version 3.3.7.25). We analysed the relevant actions typically used during offensive phases, including: passes to teammates, crosses into the penalty box and ball receptions. The results suggest that players` interactive behaviours within a football match support the existence of a scale free network. Defenders and midfielders are the athletes presenting the highest level of connectivity with their teammates. It was concluded that network analysis might be useful to shed some light on the individual contributions to the collective team performance and provide insights on how creative and organizing individuals might act to orchestrate team strategies. This suggests that the proposed methodology can be used to characterize the collective behaviours that emerge through cooperation and competition between players during football matches.